Enhanced mechanical performance of grain boundary precipitation-hardened high-entropy alloys via a phase transformation at grain boundaries. (30th September 2021) - Qi, Y.L.; Zhao, L.; Sun, X.; Zong, H.X.; Ding, X.D.; Jiang, F.; Zhang, H.L.; Wu, Y.K.; He, L.; Liu, F.; Jin, S.B.; Sha, G.; et al.
Graphical abstract: Highlights: A new strategy of designing local stress concentration-induced phase transformation at grain-boundary regions. Experiments and molecular dynamic (MD) simulations unveil the mechanisms of tensile deformation. A superior combination of high strength and high ductility at ambient temperature. Abstract: Grain-boundary (GB) precipitation has a significant adverse effect on plasticity of alloys, which easily leads to catastrophic intergranular failure in safety-critical applications under high external loading. Herein, we report a novel strategy that uses the local stress concentration induced by GB precipitates as a driving force to trigger phase transformation of preset non-equiatomic high-entropy solid-solution phase at GBs. This in situ deformation-induced phase transformation at GBs introduces a well-known effect: transformation-induced plasticity (TRIP), which enables an exceptional elongation to fracture (above 38 %) at a high strength (above 1.5 GPa) in a GB precipitation-hardened high-entropy alloy (HEA). The present strategy in terms of "local stress concentration-induced phase transformations at GBs" may provide a fundamental approach by taking advantage of (rather than avoiding) the GB precipitation to gain a superior combination of high strength and high ductility in HEAs.